Using a planetarium fieldtrip to engage young children in three-dimensional learning through representations, patterns, and lunar phenomena. Issue 3 (3rd July 2018) - Plummer, Julia D.; Small, Kim J.
ABSTRACT: Fieldtrips to informal science institutions can be opportunities for children to engage in three-dimensional learning, which is the integration of core disciplinary ideas, science practices, and cross-cutting concepts. We explored the question of whether the combination of a planetarium fieldtrip and classroom lessons could support young children's three-dimensional learning in astronomy. We assessed first grade students' (6–7-year-olds; N = 46) three-dimensional learning at the intersection of lunar phenomena, representational practices, and patterns. Students' were interviewed, where they both described their understanding verbally and constructed representations, before the intervention, after the intervention, and one year later. A mixed-methods analysis demonstrated significant improvement in students' three-dimensional learning, focused on the apparent daily motion of the Moon and lunar phases. Analysis of both interview results and audio/video of the intervention suggest that the planetarium fieldtrip provided students with a source of evidence for concepts and patterns related to scientific phenomena, which was then the subject of further inquiry in the classroom as students integrated new science concepts and patterns with their own ideas for how to create scientific representations. These findings suggest that fieldtrips, when supported by students' classroom experiences, can serve an important role in engaging young children in three-dimensional learning and thus pointing to ways that informal science venues can work with formal educators to engage students in doing science.